The Cultural, Pharmacological, and Spiritual Significance of Tri Ketuka in Balinese Healing and Yoga - I Made Sugata; I Gusti Agung Ayu Kartika; Dewi Puspita Apsari; I Gusti Ngurah Agung Windra Wartana Putra (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
This study delves into the cultural, pharmacological, and spiritual significance of Tri Ketuka, a traditional Balinese polyherbal formulation composed of Acorus calamus, Cryptocarya massoy, and Allium sativum, as documented in classical Usadha manuscripts. These three plants are not only known for their therapeutic properties but also for their symbolic role in promoting balance and holistic well-being within Balinese healing and yoga traditions. This qualitative study employed document analysis to investigate the use of Tri Ketuka in both healing rituals and yoga-based practices, particularly the Jala Neti nasal cleansing technique. The analysis is supported by illustrative testimonial evidence from users. The findings underscore the medicinal, spiritual, and cultural value of Tri Ketuka, affirming its relevance in both traditional and modern wellness contexts. The study also highlights the potential for integrating Balinese traditional medicine into contemporary healthcare as part of alternative and complementary therapies.